(untitled) (Research, Society and Development, 2022)
The objective of this experiment was to evaluate the benefits of acetic acid in different periods of inclusion in broiler drinking water on broiler performance, pH, and microbiota, especially the morphometry of the jejunum of broiler chickens. For this, 240 chickens of the Cobb500® lineage of 21 days of age were used and distributed in boxes in an experimental broiler house, considering a completely randomized design, with four treatments and four replications of 15 birds each (experimental unit). The treatments were: T1 - Control (chlorinated water at 3 ppm); T2 - chlorinated and acidified water with acetic acid in the period from 21 to 42 days of age; T3- chlorinated and acidified water with acetic acid in the period from 28 to 42 days of age; T4 - chlorinated and acidified water with acetic acid in the period from 35 to 42 days of age. The results were analyzed using Analysis of Variance, followed by Tukey’s post-test, considering a significance level of 5%. No differences in performance were observed in the period from 21 to 42 days of age, pH, and Lactobacillus spp. counts of the crop at 42 days of age and height of villi and jejunum crypt depth in the same age. However, there was a reduction (P<0.05) in the enterobacteria count in the crop at 42 days of age, which could contribute to the reduction of intestinal enterobacteria counts and, in turn, reduce the contamination of the carcass of broiler chickens.